Sourcing misfortunes: translation and tragedy - Brown, F (McMaster University, 2021)
From its first review to recent scholarship, critics have derided and dismissed the use made of translation in The Misfortunes of Arthur (1588). This essay reconsiders how the play approaches imitation by examining its translations from Senecan tragedy and Lucan’s De Bello Civili (ca 61-5 CE). With particular emphasis on Misfortunes’s ghost sequences and Oedipal echoes, this approach reveals the play’s engagement not just with the pedagogy and politics of Elizabethan England but also with innovations in dramatic form.